Production and Quality Levels of Construction Materials in Andean Regions: A Case Study of Chimborazo, Ecuador - Cevallos, Oscar A.; Jaramillo, David; Ávila, Carlos; Aldaz, Ximena (Penerbit Universiti Sains Malaysia, 2017)
An important economic activity in the province of Chimborazo is the manufacturing and production of construction materials such as clay bricks, blocks, pavers and petrous materials (aggregates). These materials must meet minimum quality requirements to ensure proper mechanical behaviour and prolong the lifespan of civil construction projects. In this study, the quality of clay bricks, concrete blocks, paving bricks and natural aggregates for concrete produced in all the factories of the province from 2012 to 2015 was assessed. The results obtained were compared with the quality standards provided by the Ecuadorian Institute of Standardization (INEN). All testing procedures for the characterisation of physical and mechanical properties followed the guidelines set by the American Society for Testing and Materials (ASTM) and the British Standards Institution (BSI). This study presents the outcomes of the quality evaluation of construction materials produced in 258 factories located in the 10 districts (cantons) of Chimborazo. The study revealed that paving bricks and aggregates for concrete performed better than clay bricks and concrete blocks. The concrete block samples had the highest percentage of noncompliance with the specifications and the widest spread of the results. Quality problems in the production of construction materials were found in all the districts of Chimborazo.